Gender Diversity in Digital Games: a Tertiary Literature Review - Batista, Estela Miranda; Silva, Thais Regina De Moura Braga; Silva, Gláucia Braga E (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: The digital games industry, although still not very diverse in terms of gender, has affected the lives of millions of people every day, both economically and in their personal experiences and relationships. Problem: Although women and men play video games in approximately equal numbers, female representation as characters and, specially, as game producers is very unbalanced in the Brazilian gaming industry. Solution: We present a tertiary mapping of the literature summarizing the main advances in dealing with female representation in digital games with the aim of identifying gaps and suggest areas for future research. IS Theory: Equity Theory. Method: We conducted a Tertiary Literature Review applied to 6 scientific bases with the aim of answering the following research question: what are the main themes regarding gender diversity in research on digital games?. Summary of Results: We collected and analyzed 5 secondary studies to gain an understanding of this research domain. The results reveal that, in terms of character design and general characteristics, the games appear stereotypical and often even misogynistic in relation to the female gender. Furthermore, they also highlight the low number of games developed specifically for women. Finally, few studies have addressed the low representation in digital game development teams. Contributions and Impact in the area of IS: This study contributes to the field of IS by establishing an overview of the state of the art in the literature regarding gender equity in the digital games industry.